Socializing Distrust of the Justice System through the Family in Juvenile Delinquency Court. (29th December 2016) - Pennington, Liana
Abstract : Juvenile delinquency courts in the United States generally require parents to attend all court hearings, but little is known about how parents' experiences in the court process affect their discussions of the justice system with their court‐involved children. Using multiperspectival and longitudinal data combining observations with interviews of parents and youth in two courts, this research finds that many parents discuss the legal process in negative terms with their children when parents are outside the presence of legal authorities. This research adds to the literature on legal socialization by examining how parents' perceptions of law and their experiences with the court become part of the socializing content provided by parents to their court‐involved children. Creating a more meaningful role for parents in the juvenile justice process may potentially lead to more positive discussions of the court process between parents and juvenile defendants.